Elves in Anglo-Saxon England : matters of belief, health, gender and identity - Hall, Alaric (Anglo-Saxon studies, 2007)
Anglo-Saxon elves (Old English ælfe) are one of the best attested non-Christian beliefs in early medieval Europe, but current interpretations of the evidence derive directly from outdated nineteenth- and early twentieth-century scholarship. Integrating linguistic and textual approaches into an anthropologically-inspired framework, this book reassesses the full range of evidence. It traces continuities and changes in medieval non-Christian beliefs with a new degree of reliability, from pre-conversion times to the eleventh century and beyond, and uses comparative material from medieval Ireland and Scandinavia to argue for a dynamic relationship between beliefs and society. In particular, it interprets the cultural significance of elves as a cause of illness in medical texts, and provides new insights into the much-discussed Scandinavian magic of seidr. Elf-beliefs, moreover, were connected with Anglo-Saxon constructions of sex and gender; their changing nature provides a rare insight into a fascinating area of early medieval European culture